ChemInform Abstract: Geometric Isomerism in Coordination Cages Based on Tris‐chelate Vertices: a Tool to Control Both Assembly and Host/Guest Chemistry. Issue 50 (November 2016) - Metherell, Alexander J.; Ward, Michael D.
Abstract: Review: 77 refs.